A new offshore transport mechanism for shoreline‐released tracer induced by transient rip currents and stratification. Issue 6 (25th March 2017) - Kumar, Nirnimesh; Feddersen, Falk
Abstract: Offshore transport from the shoreline across the inner shelf of early‐stage larvae and pathogens is poorly understood yet is critical for understanding larval fate and dilution of polluted shoreline water. With a novel coupling of a transient rip current (TRC) generating surf zone model and an ocean circulation model, we show that transient rip currents ejected onto a stratified inner shelf induce a new, previously unconsidered offshore transport pathway. For incident waves and stratification typical for Southern California in the fall, this mechanism subducts surf zone‐origin tracers and transports them at least 800 m offshore at 1.2 km/d analogous to subduction at ocean fronts. This mechanism requires both TRCs and stratification. As TRCs are ubiquitous and the inner shelf is often stratified, this mechanism may have an important role in exporting early‐stage larvae, pathogens, or other tracers onto the shelf. Plain Language Summary: The principal offshore transport pathway of shoreline‐released intertidal larvae and pathogens within 1 km of the coast is still a mystery, motivating this study. Here a new offshore transport pathway for shoreline pollution and shoreline‐released intertidal invertebrate larvae from the surf zone to 1 km offshore is presented. This new and intuitive offshore transport pathway will help provide insight to abundance of offshore larvae and marine population connectivity. This transport pathway is induced by transient rip currents (TRCs, episodic offshore flow from the surf zone) and stratification (temperature difference with depth) and leads to offshore advection of 1.2 km/d. The findings are based on a new model that couples TRC generation to a three‐dimensional ocean circulation model. Previous models lacked the TRC‐generating mechanism and miss this pathway. Without TRCs the offshore transport is only about 5% of that with TRCs. Study findings have implications for marine population connectivity, marine‐protected area design, and export of pathogens, contaminants, and nutrients. Key Points: Transient rip currents induce offshore tracer transport of 1.2 km/d on a stratified inner shelf Without transient rip currents, offshore transport is reduced 95% This mechanism may be important in exporting larvae, pathogens, or other tracers to the inner shelf